2007
DOI: 10.1111/j.1540-5915.2007.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

The FAIRSERV Model: Consumer Reactions to Services Based on a Multidimensional Evaluation of Service Fairness

Abstract: The current dominant conceptualization of consumer reactions to services is the SERVQUAL model. This article proposes the FAIRSERV model as an alternative or additional conceptualization of consumer reactions to services. FAIRSERV involves seeing service evaluation through the lens of organizational fairness (justice) theory applied to the relationship between the service consumer and the service provider. FAIRSERV is premised on the claim that, especially in relational service contexts, consumers are interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
173
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(189 citation statements)
references
References 69 publications
5
173
0
7
Order By: Relevance
“…Further, this study expands previous fairness studies by supporting that these four factors of fairness can form a second-order factor of overall fairness . This result is in line with previous studies, 4,8,34 which identifi ed signifi cant correlations among fairness dimensions. The second-order construct refl ects the sales transactions with multiple activities, 34 which can infl uence customers ' perception of overall fairness.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Further, this study expands previous fairness studies by supporting that these four factors of fairness can form a second-order factor of overall fairness . This result is in line with previous studies, 4,8,34 which identifi ed signifi cant correlations among fairness dimensions. The second-order construct refl ects the sales transactions with multiple activities, 34 which can infl uence customers ' perception of overall fairness.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Skarlicki 8 found that the four dimensions of justice are correlated with one another with a minimum correlation of 0.22 in a university setting, and with a minimum correlation of 0.14 in an organizational setting. Carr 34 also found that the four types of fairness are inter-correlated with one another (minimum correlation: 0.33). These prior studies hint that the four types of fairness may share a root of overall fairness.…”
Section: Hypothesismentioning
confidence: 92%
See 1 more Smart Citation
“…These five dimensions used to Carr (2007) proposed an important deficiency of SERVQUAL scale by stating that it does not include equity theory as the basis for any of its scales, even if it is clear from previous experience that equity (fairness) is often evaluated in service encounters. FAIRSERV (Carr, 2007), in conjunction with SERVQUAL (Parasuraman et al 1988), may be suitable for this study, due to its focus on satisfaction and loyalty intensions. The preliminary questionnaire is on five attributes of SERVQUAL scale and "Systematic Fairness" dimension of FAIRSERV model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A survey instrument was developed based on an extensive review of literature on different aspects of service quality measurement with a focus on employee related issues using a combination of SERVQUAL (Parasuraman et al, 1985(Parasuraman et al, , 1988 and FAIRSERV (Carr, 2007) scales. The questionnaire was refined after focus group discussion with five managers working in different SMEs and three academicians with work published in similar area.…”
Section: Fig 2 Relationship Between Independent Mediating and Depementioning
confidence: 99%